Influence of satisfaction with family life and child-parental violence on school satisfaction among Peruvian high school students - Rodríguez Guevara, Magali (2026)
Background: Within the family context, one of the problems that has gained particular relevance in adolescence is child-to-parent violence, understood as physical, verbal, or psychological behaviors perpetrated by children against their parents. Despite existing evidence, a knowledge gap persists regarding the combined effect of family life satisfaction and child-to-parent violence on school satisfaction, especially in Latin American contexts. Objective: This study aimed to determine the association between satisfaction with family life and child-to-parent violence on school satisfaction among secondary school students in Nueva Cajamarca, Peru. Method: An analytical-correlational study was conducted, testing a structural model of relationships between variables using SEM. Participants were selected through non-probability sampling, including 497 secondary school students from Nueva Cajamarca, Peru. Result: The average age was 14 years, with the majority being female (255 students, or 51.3%), and 276 students (55.5%) reporting living with both parents. The instruments used were the High School Satisfaction Scale (H-SatP Scale), the Brief Child-to-Parent Violence Scale, and the Satisfaction with Family Life Scale (SWFLS). Conclusion: The results revealed that satisfaction with family life had a significant positive effect on school satisfaction, while child-to-parent violence had a negative effect. This suggests that satisfaction with family life serves as a protective factor for school satisfaction, while child-to-parent violence represents a risk factor for school satisfaction.